2014
DOI: 10.1177/0192513x14541444
|View full text |Cite
|
Sign up to set email alerts
|

Parental Involvement With College Students in Germany, Hong Kong, Korea, and the United States

Abstract: Rates of college attendance have increased throughout the world. This study asked whether students across nations experience high involvement with parents (frequent contact and support) and how satisfied they are with parental involvement. College students from four major Western and Asian economies participated: Germany (n = 458), Hong Kong (n = 276), Korea (n = 257), and the United States (n = 310). Consistent with solidarity theory, students across nations reported frequent contact with parents and receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 43 publications
6
40
0
1
Order By: Relevance
“…Underscoring interdependence among family members during this joint transition phase (Scabini et al, 2006), parents and children appeared to be significant sources of support for each other (Bucx, van Wel, & Knijn, 2012), even though it was demonstrated that current support was predominantly provided by parents to children (Bucx et al, 2012; Fingerman et al, 2016). Different forms of support were identified (e.g., emotional, practical, companionship, advice; Fingerman et al, 2016; Kloep & Hendry, 2010; Napolitano, 2015), often including financial assistance. Faw, Sonne, and Leustek (2019) advanced tough love as a form of parent–child support, underscoring that communicating parent–offspring support was extremely important.…”
Section: Family Dynamics During Emerging Adulthood: What We Already Knowmentioning
confidence: 99%
“…Underscoring interdependence among family members during this joint transition phase (Scabini et al, 2006), parents and children appeared to be significant sources of support for each other (Bucx, van Wel, & Knijn, 2012), even though it was demonstrated that current support was predominantly provided by parents to children (Bucx et al, 2012; Fingerman et al, 2016). Different forms of support were identified (e.g., emotional, practical, companionship, advice; Fingerman et al, 2016; Kloep & Hendry, 2010; Napolitano, 2015), often including financial assistance. Faw, Sonne, and Leustek (2019) advanced tough love as a form of parent–child support, underscoring that communicating parent–offspring support was extremely important.…”
Section: Family Dynamics During Emerging Adulthood: What We Already Knowmentioning
confidence: 99%
“…A robust body of literature indicates that parents provide considerable financial support (Schoeni and Ross 2005;Yelowitz 2007) and frequently listen to their children and give them advice, typically around a few times a month, during emerging and young adulthood (Fingerman et al 2016(Fingerman et al , 2009(Fingerman et al , 2010Pettit et al 2011). Theories of intergenerational support (Antonucci and Akiyama 1987;Becker 1981) identify four reasons for parents' continuance of support: (a) to help children in need (altruism), (b) to maximize reproductive success (evolution), (c) to derive support from children in older adulthood (exchange), and (d) to improve chances for success (investment).…”
Section: Developmental Psychology Literature Characterizing Parental mentioning
confidence: 99%
“…This point is especially relevant for college students, who are most often living away from home for the first time in their lives (Arnett 2006). A growing body of literature has documented that college students and their parents utilize the internet and the cell phone to communicate on a frequent basis, and that most students use communication technologies to support positive family relationships (Aoki and Downes 2003;Chen and Katz 2009;Fingerman et al 2016;Gentzler et al 2011;Stafford and Hillyer 2012;Smith et al 2012). For example, Chen and Katz (2009) found that students reported that their cell phone was the most important tool for keeping in touch with their parents because it enabled direct and instantaneous contact, despite geographical distance.…”
Section: Developmental Psychology Literature Characterizing Parental mentioning
confidence: 99%
“…Although there are differences in how collectivistic traits manifest in greater society, traits and attitudes towards educational experiences are often shared. For instance, higher education students in Hong Kong and South Korea report more financial and social support than those in Germany and the USA, and like Japan, students in these East Asian contexts tend to live with their families while studying (Fingerman, Cheng, Kim, Fung, Han, Lang and Wagner, 2014). Some aspects of the Japanese self-selection criteria (e.g.…”
Section: Applying Self-selection To East Asian Contextsmentioning
confidence: 99%